Exercise performance and fatiguability in patients with chronic fatigue syndrome. Issue 9 (September 1993) - Gibson, H; Carroll, N; Clague, J E; Edwards, R H
Abstract : To examine the role of delay in recovery of peripheral muscle function following exercise in the fatigue experienced by patients with the chronic fatigue syndrome (CFS) and to examine the influence of effort perception in limiting exercise performance in these patients, a study was carried out on a group of twelve patients with chronic fatigue syndrome and 12 sex and age-matched sedentary control subjects. Symptom limited incremental cycle exercise tests including measurements of perceived exertion were performed followed by examination of the contractile properties of the quadriceps muscle group for up to 48 hours. Muscle function was assessed by percutaneous electrical stimulation and maximum voluntary contractions. Muscle function at rest and during recovery was normal in CFS patients as assessed by maximum isometric voluntary contraction, 20:50 Hz tetanic force ratio and maximum relaxation rate. Exercise duration and the relationship between heart rate and work rate during exercise were similar in both groups. CFS patients had higher perceived exertion scores in relation to heart rate during exercise representing a reduced effort sensation threshold of 3.2 units on an unmodified Borg scale in CFS patients. Patients with chronic fatigue syndrome show normal muscle physiology before and after exercise. Raised perceived exertion scores during exercise suggest that central factors are limiting exercise capacity in these patients.